An Analysis of Metaphor Translation in Anthony Capella's Novel Titled "The Various Flavors of Coffee" - Dewi, Putri Andam (2014)
Various Flavors of Coffee". The aims of the study are to identify the types of metaphor and the strategies in translating metaphors employed in the novel. This study also determines the quality of metaphor translation in the novel. This study combined two methods of research namely qualitative and quantitative. The qualitative data were obtained through document analysis. The data collected from document This study discusses the issue of metaphor translation presented in the novel "The analysis were categorized into two types of metaphors and five strategies of translating it by using Larson's theory (1984). Meanwhile, the quantitative data were obtained through questionnaire filled by the respondents. The questionnaire consisted of six questions which are in Likert scale form. The data were analyzed by using IBM SPSS 20.0 in order to determine the quality level of the metaphor translation. This study found out that in all of metaphors involved in novel "The Various Flavors of Coffee", live metaphors are more frequently applied rather than dead metaphors. This study also identified the strategies in translating metaphors in the novel. From five strategies proposed by Larson (1984), the metaphors were mostly transferred by keeping the metaphors directly without making any changes. This study revealed that the quality of those metaphors' translation is "good". It fulfilled six criteria of translation namely grammaticality, accuracy, terminology, consistency, cultural identity, and overall impression. After conducting this study, the author recommends a further research in deeper scope of translating metaphors, such as investigating the relationship between the strategies of metaphors' translation and the translator competence. In addition, this study was expected to give some valuable information and reference to the readers, the translating major students, and the translators related to metaphors' translation.